A late Caledonian tectono-thermal event in the Gaissa Nappe Complex, Arctic Norway: evidence from fine-fraction K‒Ar dating and illite crystallinity from the Digermulen Peninsula. (2nd October 2019) - Meinhold, Guido; Wemmer, Klaus; Högström, Anette E. S.; Ebbestad, Jan Ove R.; Jensen, Sören; Palacios, Teodoro; Høyberget, Magne; Agić, Heda; Taylor, Wendy L.
ABSTRACT: Fine-fraction K‒Ar dating and illite crystallinity determination were applied on a peculiar pale olive green shale sample from the upper Ediacaran Indreelva Member (Stáhpogieddi Formation, Vestertana Group, Gaissa Nappe Complex) of the Digermulen Peninsula in Finnmark, Arctic Norway, to constrain the age and metamorphic conditions of tectono-thermal overprint. The <2 and <0.2 µm grain-size fractions are almost purely illite and yielded an illite crystallinity (expressed as the Kübler index) of 0.215 Δ° 2 θ and 0.228 ∆° 2 θ and K‒Ar ages of 403.9 ± 4.2 and 391.5 ± 4.0 Ma, respectively. The K‒Ar ages are interpreted to present late-stage thermal overprint under low epizonal conditions along a localised shear zone, likely post-dating the peak of metamorphism and cleavage generation on the Digermulen Peninsula. Thus, a later tectono-metamorphic event related to the late stage of the Scandian orogeny is locally recorded in the Gaissa Nappe Complex of the Caledonides of Finnmark. This late Scandian event was probably caused by orogenic extensional collapse and appears to have extended at least into Mid-Devonian time.